Loneliness during the COVID-19 Pandemic: Evidence from Five European Countries - Anthony Lepinteur; Alessio Rebechi; Andrew E. Clark; Conchita D'Ambrosio; Nicholas Rohde; Claus Vögele (Institute of Labor Economics (IZA), 2024)
We use quarterly panel data from the COME-HERE survey covering five European countries to analyse three facets of the experience of loneliness during the COVID-19 pandemic. First, in terms of prevalence, loneliness peaked in April 2020, followed by a U-shape pattern in the rest of 2020, and then remained relatively stable throughout 2021 and 2022. We then establish the individual determinants of loneliness and compare them to those found in the literature predating the COVID-19 pandemic. As in previous work, women are lonelier, and partnership, education, income, and employment protect against loneliness. However, the pandemic substantially shifted the age profile: it is now the youngest who are the loneliest. We last show that pandemic policies affected loneliness, which rose with containment policies but fell with government economic support. Conversely, the intensity of the pandemic itself, via the number of recent COVID-19 deaths, had only a minor impact. The experience of the pandemic has thus shown that public policy can influence societal loneliness trends.
Keywords: H51; I18; I31; 330; age; COME-HERE; COVID-19; loneliness; pandemic policies